PENGARUH PELATIHAN PENINGKATAN KOMPETENSI DAN MOTIVASI TERHADAP KINERJA GURU SMKN 4 BOJONEGORO - jurnalmap map; Muhammad Syamsul Anam; Indra Prasetyo (MAP (Jurnal Manajemen dan Administrasi Publik), 2019)
ABSTRACT This study aims to analyze the description and influence of both the training on improving competence, motivation and performance of teachers at SMK Negeri 4 Bojonegoro. The population in this study were all teachers of SMK Negeri 4 Bojonegoro who teached assignments at the time the research was conducted. The total population is 66 people. The sampling technique used was census sampling. The sampling census in this study was all members who became the study sample. The samples in this study were 66 SMK Negeri 4 Bojonegoro teachers. The data analysis technique used in this study is In this study, the analysis technique used was simple linear regression. The results of the data analysis showed an increase in competence, teacher motivation and the performance of Bojonegoro Vocational High School 4 teachers in good categories. The training to improve the competency and motivation of teachers together significantly increased the performance of the teachers of SMK 4 Bojonegoro. The training to increase the competence and motivation of each teacher partially pushed significantly towards the performance of teachers in Bojonegoro 4 Vocational High School. Among the training on increasing competency and motivation of teachers who have a dominant influence on teacher performance at Bojonegoro 4 Vocational School is teacher motivation. Keywords: training in increasing competence, motivation, performance